En Bloc Resection Versus Conventional TURBT for T1HG Bladder Cancer: A Propensity Score-Matched Analysis - Yanagisawa, Takafumi; Matsukawa, Akihiro; Iwatani, Kosuke; Sato, Shun; Hayashida, Yasushi; Okada, Yohei; Yorozu, Takashi; Fukuokaya, Wataru; Sakanaka, Keigo; Urabe, Fumihiko; Kimura, Shoji; Tsuzuki, Shunsuke; et al. (Annals of surgical oncology, 2023)
BACKGROUND: We aimed to assess the clinical, oncological, and pathological impact of en bloc resection of bladder tumors (ERBT) compared with conventional transurethral resection of bladder tumors (cTURBT) for pT1 high-grade (HG) bladder cancer. PATIENTS AND METHODS: We retrospectively analyzed the record of 326 patients (cTURBT: n = 216, ERBT: n = 110) diagnosed with pT1 HG bladder cancer at multiple institutions. The cohorts were matched by one-to-one propensity scores based on patient and tumor demographics. Recurrence-free survival (RFS), progression-free survival (PFS), cancer-specific survival (CSS), and perioperative and pathologic outcomes were compared. The prognosticators of RFS and PFS were analyzed using the Cox proportional hazard model. RESULTS: After matching, 202 patients (cTURBT: n = 101, ERBT: n = 101) were retained. There were no differences in perioperative outcomes between the two procedures. The 3-year RFS, PFS, and CSS were not different between the two procedures (p = 0.7, 1, and 0.7, respectively). Among patients who underwent repeat transurethral resection (reTUR), the rate of any residue on reTUR was significantly lower in the ERBT group (cTURBT: 36% versus ERBT: 15%, p = 0.029). Adequate sampling of muscularis propria (83% versus 93%, p = 0.029) and diagnostic rates of pT1a/b substaging (90% versus 100%, p < 0.001) were significantly better in ERBT specimen compared with cTURBT specimen. On multivariable analyses, pT1a/b substaging was a prognosticator of disease progression. CONCLUSIONS: In patients with pT1HG bladder cancer, ERBT had similar perioperative and mid-term oncologic outcomes compared with cTURBT. However, ERBT improves the quality of resection and specimen, yielding less residue on reTUR and yielding superior histopathologic information such as substaging.
Keywords: tendenční skóre; urologické chirurgické výkony; Propensity Score; Urinary Bladder Neoplasms; Urologic Surgical Procedures; Cystectomy; retrospektivní studie; Humans; Retrospective Studies; nádory močového měchýře; lidé; cystektomie